2012
DOI: 10.5402/2012/906761
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide as a Microbial Toxicity Enhancer of Some Antibacterial Agents: A New Potential Water Purification Tool

Abstract: The aim of current paper was to investigate the possibility of increasing the toxicity of calcium hypochlorite (Ca(ClO)2) and hydrogen peroxide (H2O2) onEscherichia coli K-12by preliminary enrichment of culture media by carbon dioxide (CO2). For this purpose, the microbes sensitivity to H2O2or/and Ca(ClO)2at normal and CO Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The increase in the lethality of Cl 2 solutions against E. coli and L. monocytogenes with the incorporation of CO 2 MNBs compared to the other gases can be attributed to the ability of CO 2 to form carbonic acid in aqueous solutions and thus increasing the ability of AMs to penetrate through the bacterial cell membranes (Martirosyan et al . 2012). Martirosyan et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the lethality of Cl 2 solutions against E. coli and L. monocytogenes with the incorporation of CO 2 MNBs compared to the other gases can be attributed to the ability of CO 2 to form carbonic acid in aqueous solutions and thus increasing the ability of AMs to penetrate through the bacterial cell membranes (Martirosyan et al . 2012). Martirosyan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Martirosyan et al . (2012) used CO 2 along with calcium hypochlorite against E. coli and concluded that CO 2 could penetrate the microbial cells easily, thus increasing the sensitivity of microbes to the toxic effect of calcium hypochlorite. Sikin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moist, warm CO 2 gas could become a competitive disinfection technology. Carbon dioxide gas is an antiviral, antibacterial, and anti-infection agent effective not only on solid surfaces but also in aqueous solutions and water treatment settings (17). Heated, un-pressurized carbon dioxide bubbled through wastewater or aqueous media effectively destroys both waterborne bacteria and viruses (18).…”
Section: Universal Virucidal and Antimicrobial Activitymentioning
confidence: 99%
“…Supercritical CO 2 offers a novel, user-friendly process to sterilize acellular tissue, such as lung matrices, for use in tissue and organ engineering (22). CO 2 can also enhance the effect of some other antibacterial agents, further improving the protection imparted (17). When breathing is impaired, CO 2 -levels in the human body drop, which creates a favorable environment for bacterial growth and a higher risk of infection.…”
Section: Universal Virucidal and Antimicrobial Activitymentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) is a basic biogas and has been used for clinical purposes for over a century due to its unique properties [ 4 ]. CO 2 can also enhance the effect of some other germ-destroying agents which further improves the protection imparted [ 5 ]. Irving Langmuir first coined the term ‘plasma’ in 1927 to describe an ionized gas [ 6 ].…”
Section: Introductionmentioning
confidence: 99%